INDUSTRI PERBANKAN SYARIAH DI INDONESIA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH - Effendi, Arif (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractIslamic Banking is banking or banking activity that is consistent with the principles of Islamic law (Sharia) which prohibit specific interest or fee known as riba or usury for loans of money. Islamic Banking grew and developed in Indonesia with the establishment of Indonesia Muamalat Bank. In Indonesia, the Islamic Banking system is regulated by the enactment of the Law Number 21 of 2008 Concerning Sharia Banking which regulates Islamic Banking more comprehensive than the Law Number 10 of 1998 Concerning Banking which regulates conventional banking or banking generally.The fact that Indonesia has the world’s largest Muslim population creates a huge market for sharia banking, and Indonesia Muamalat Bank has become the pioneer that made a breakthrough in the existing concept of banking. That is why  to operate  Islamic Bank has a good prospect in Indonesia. Islamic Bank operates no interest, but it is operated by using the concept of risk sharing or profit loss sharing.There are two objectives of the study we want to know, that are :First, wish to know the description of Islamic Banking in Indonesia according to the Law Number 21 of 2008 Concerning Sharia Banking and the growth of Islamic Banking from year to year especially after the enactment of the Law Number 21 of 2008 Concerning Sharia Banking.Second, wish to know how the opportunity and the prospect of Islamic Banking in   Indonesia since it is regulated by the Law Number 21 of 2008 Concerning Sharia BankingKeywords: Islamic banking, Sharia principles, Banking industry, Prospect